2018
DOI: 10.1371/journal.pone.0204753
|View full text |Cite
|
Sign up to set email alerts
|

Trophic structure and energy flow in a shallow-water hydrothermal vent: Insights from a stable isotope approach

Abstract: Shallow-water hydrothermal vent ecosystems are distinct from the deep-sea counterparts, because they are in receipt of sustenance from both chemosynthetic and photosynthetic production and have a lack of symbiosis. The trophic linkage and energy flow in these ecosystems, however remain elusive, which allows us poor understanding of the whole spectrum of biological components distributed across such environmental gradients. In this study, a thorough isotopic survey was conducted on various biological specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 66 publications
4
40
3
Order By: Relevance
“…detritus [24,27]. The sulfur-rich sediments and vent water contained high diversity of bacterial communities and chemoautotrophic populations in the hydrothermal vent area [31,32].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…detritus [24,27]. The sulfur-rich sediments and vent water contained high diversity of bacterial communities and chemoautotrophic populations in the hydrothermal vent area [31,32].…”
Section: Plos Onementioning
confidence: 99%
“…Specimens of this crab were firstly discovered from fishery bycatches [14]. Later there were several related research reports on it, such as on its detoxification mechanism [17], bioaccumulation of trace metals [22], metabolic energy demands, and food utilization [23], feeding [24][25], selective behavior [26], role in the trophic structure [27][28], and reproduction [28]. However, although this species has been exploited during two decades, the in situ distribution pattern and many aspects of biology of this crab in the hydrothermal vent area has not been understood.…”
Section: Introductionmentioning
confidence: 99%
“…Although ecologists have monitored food webs around shallow vents under relatively stable environmental conditions, no studies have yet examined how food webs respond to extreme events using data collected before and after drastic biogeochemical disruptions (11)(12)(13)(14). To improve environmental management and protection of hydrothermal ecosystems, it is important understanding how vent benthic fauna respond to a transition from active to inactive, and how they rely on resources from surrounding non-chemosynthetic ecosystems (15).…”
Section: Introductionmentioning
confidence: 99%
“…Its successful existence in the YV has been attributed to its physiological adaptation to highly acidic and toxic hydrothermal fluids (19,22,23). Although vent crabs are closely associated with toxic sulfur vent habitats, it is unclear whether they are obligate feeders of sulfur bacteria because vent crabs also rely on substantial contributions from photosynthetic derived sources by feeding on dead zooplankton, detritus and biofilms on vent rocks (11)(12)(13)(14). Compared to YV, the less hostile WV has a much higher faunal diversity (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…New species are discovered, and important ecological insights emerge, on every expedition. Recent studies revealed that hydrothermal vent communities in the EEZ of the Kingdom of Tonga are stable over long timescales (Du Preez and Fisher, 2018); that hydrothermal vent ecosystems can act as nursery grounds for non-vent species (Salinas- de-León et al, 2018); and that shallow-water hydrothermal vents may play a greater role in trophic ecology than previously suspected (Chang et al, 2018). Given the advancement of the nascent deep-sea mining industry, research must accelerate.…”
Section: Implications For Deep-sea Miningmentioning
confidence: 99%